Enemy in the Mirror : Islamic Fundamentalism and the Limits of Modern Rationalism: A Work of Comparative Political Theory - Euben, Roxanne L. (Book collections on Project MUSE., 2001)
A firm grasp of Islamic fundamentalism has often eluded Western political observers, many of whom view it in relation to social and economic upheaval or explain it away as an irrational reaction to modernity. Here Roxanne Euben makes new sense of this belief system by revealing it as a critique of and rebuttal to rationalist discourse and post-Enlightenment political theories. Euben draws on political, postmodernist, and critical theory, as well as Middle Eastern studies, Islamic thought, comparative politics, and anthropology, to situate Islamic fundamentalist thought within a transcultural t.